Regulatory Dynamics of Plant Hormones and Transcription Factors under Salt Stress - Muhammad Aizaz; Lubna; Rahmatullah Jan; Sajjad Asaf; Saqib Bilal; Kyung-Min Kim; Ahmed AL-Harrasi (Biology)
The negative impacts of soil salinization on ion homeostasis provide a significant global barrier to agricultural production and development. Plant physiology and biochemistry are severely affected by primary and secondary NaCl stress impacts, which damage cellular integrity, impair water uptake, and trigger physiological drought. Determining how transcriptional factors (TFs) and hormone networks are regulated in plants in response to salt stress is necessary for developing crops that tolerate salt. This study investigates the complex mechanisms of several significant TF families that influence plant responses to salt stress, involving AP2/ERF, bZIP, NAC, MYB, and WRKY. It demonstrates how these transcription factors (TFs) help plants respond to the detrimental effects of salinity by modulating gene expression through mechanisms including hormone signaling, osmotic stress pathway activation, and ion homeostasis. Additionally, it explores the hormonal imbalances triggered by salt stress, which entail complex interactions among phytohormones like jasmonic acid (JA), salicylic acid (SA), and abscisic acid (ABA) within the hormonal regulatory networks. This review highlights the regulatory role of key transcription factors in salt-stress response, and their interaction with plant hormones is crucial for developing genome-edited crops that can enhance agricultural sustainability and address global food security challenges.